2014
DOI: 10.1093/jpepsy/jsu032
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Parent and Family-Based Interventions for Children and Adolescents With Chronic Medical Conditions

Abstract: Parent- and family-based psychological therapies can improve parent outcomes, with PST emerging as particularly promising. Future research should incorporate consensus statements for outcomes assessment, multisite recruitment, and active comparator conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 82 publications
9
110
0
5
Order By: Relevance
“…Existing health care focuses largely on a medical education model which has shown limited success in improving adherence (Dean, Walters, & Hall, 2010;Ersser et al, 2014) and family-based approaches have also shown limited effects (Eccleston, Palermo Tonya, Fisher, & Law, 2012;Law, Fisher, Fales, Noel, & Eccleston, 2014). The theoretical and empirical literature provide compelling evidence that parenting plays a central role in children's health outcomes (Morawska, Calam, & Fraser, 2015;Wood et al, 2008); yet, current approaches to childhood illness management do not target parenting (Law et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Existing health care focuses largely on a medical education model which has shown limited success in improving adherence (Dean, Walters, & Hall, 2010;Ersser et al, 2014) and family-based approaches have also shown limited effects (Eccleston, Palermo Tonya, Fisher, & Law, 2012;Law, Fisher, Fales, Noel, & Eccleston, 2014). The theoretical and empirical literature provide compelling evidence that parenting plays a central role in children's health outcomes (Morawska, Calam, & Fraser, 2015;Wood et al, 2008); yet, current approaches to childhood illness management do not target parenting (Law et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Algunos programas de tratamiento basados en el modelo cognitivo-conductual han incluido a los cuidadores (padres, madres o tutores) de los niños con dolor crónico (52,53). Estas intervenciones se han contrastado en poblaciones con diferentes tipos de dolor, en estudios aleatorizados y controlados (54,55), aunque alguno incluye ensayos sin grupo control (45) y, en general, se han obtenido mejoras significativas en una amplia gama de variables, en comparación con los grupos control.…”
Section: Tratamiento Psicológico Del Dolor Crónico Infantilunclassified
“…Murphy et al 41 30,42 These vary from self-study materials and informational sessions to technical training (to develop proficiency with diabetic care procedures), motivational (individual or family) interventions, behavioral interventions to facilitate coping with stress, and support groups for patients and families. 17,30 The range of interventions is matched by the range of diverse methodologies used to test them in the literature.…”
Section: Facilitating Adherence To Testing and Diabetic Management Bementioning
confidence: 99%
“…Reviews spreading across the last 15 years highlight the lack of randomized controlled trial studies to test interventions and the overuse of cross-sectional and correlational studies. 42,43 Not surprisingly, given the inconsistency of content, methodology, and research design, literature reviews report a moderate size effect for both physiological indicators of glycemic control and psychosocial outcomes. 42 Moreover, the literature is inconsistent regarding the potential associations between behavioral outcomes (motivation, well-being, family outcomes, etc) and measures of glycemic control and balance.…”
Section: Facilitating Adherence To Testing and Diabetic Management Bementioning
confidence: 99%
See 1 more Smart Citation